2018
DOI: 10.1002/adma.201805547
|View full text |Cite
|
Sign up to set email alerts
|

Organohalide Lead Perovskites: More Stable than Glass under Gamma‐Ray Radiation

Abstract: high-throughput fabrication of perovskite modules has also been demon strated with simple processes such as blade coating with module efficiency close to 15%. [8] It remains unclear as to whether the perovskite solar cells can operate over 25 years in a real-world environment that is filled with oxygen and moisture, which are their two major stressors. Enhanced encapsulation has clearly shown to elongate the operational lifetime of perovskite solar cells to a much longer duration, indicating that the intrinsic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
111
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(115 citation statements)
references
References 32 publications
4
111
0
Order By: Relevance
“…Indeed, the combination of thin films and long carrier diffusion length allows in perovskites the efficient collection of photogenerated charges, even in the presence of defects or radiation‐induced traps, resulting in a higher radiation tolerance than thicker films and single crystals. Also, Yang et al demonstrated the excellent radiation hardness of hybrid perovskite thin layers under gamma‐ray irradiation. Such studies confirm the actual interest on perovskite solar cells and X‐ray detectors based on thin films for space application, where lightweight, large area, mechanical flexibility, and radiation hardness are crucial features as, e.g., in satellite missions.…”
Section: Comparison With the State Of The Artmentioning
confidence: 99%
“…Indeed, the combination of thin films and long carrier diffusion length allows in perovskites the efficient collection of photogenerated charges, even in the presence of defects or radiation‐induced traps, resulting in a higher radiation tolerance than thicker films and single crystals. Also, Yang et al demonstrated the excellent radiation hardness of hybrid perovskite thin layers under gamma‐ray irradiation. Such studies confirm the actual interest on perovskite solar cells and X‐ray detectors based on thin films for space application, where lightweight, large area, mechanical flexibility, and radiation hardness are crucial features as, e.g., in satellite missions.…”
Section: Comparison With the State Of The Artmentioning
confidence: 99%
“…Except for testing the performance of perovskite‐based γ‐ray detectors, Yang et. al . studied the operation stability of the hybrid perovskite Cs 0.05 FA 0.81 MA 0.14 PbI 2.55 Br 0.45 under hard γ‐rays.…”
Section: Advancement In γ‐Ray Detectorsmentioning
confidence: 99%
“…For a standard halide perovskite like CsPbI 3, the a value is 14 cm À1 which is larger than cadmium zinc tellurides (CZT) materials. [48] In contrast, the performance of CZT detectors drop significantly after exposure to 30 kGv c-irradiation. [47] In medical applications, the number of X-ray doses given to a subject to probe into a target organ should be minimized given the patient's health condition.…”
Section: X-ray and C-ray Detectorsmentioning
confidence: 99%
“…Reproduced with permission. [48] Copyright 2019, Wiley-VCH typically contain heavy atoms, are well suited to detect high energy radiations like X-ray or c-ray radiations. This is because perovskite detectors benefit from their large absorption coefficient for high energy radiation with good photoconduction properties and can be solution processed for industrial upscaling.…”
Section: X-ray and C-ray Detectorsmentioning
confidence: 99%
See 1 more Smart Citation